Classical tradition in Luis Alberto de Cuenca’s "El reino blanco" - Suárez Martínez, Luis Miguel (Cuadernos de Filología Clásica. Estudios Latinos, 2014)
This paper examines the influence of the Classical Tradition in Luis Alberto de Cuenca’s El reino blanco (2010). This influence affects both form and content. So, on the one hand, the Hellenistic epigram becomes the formal model of most of the poems in the book. Moreover, Cuenca takes from Greco-Roman culture several episodes, topics, quotes etc., that he recreates in a very personal way (often with humor and irony), in his verses, usually set in contemporary settings, and thus, away from the classical world.
Keywords: Classical Tradition; El reino blanco; Luis Alberto de Cuenca; Epigram.